2020
DOI: 10.9734/ajraf/2020/v6i330104
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Different Levels of Kolgrace Organic Fertilizer on the Growth and Yield Attributes of Greengram (Vigna radiata (L) Wilczek) in the Screenhouse

Abstract: Aim: To investigate growth and yield response of greengram to different levels of Kolgrace organic fertilizer with a view to determining the most favorable application rate for greengram production. Study Design: Completely randomized design (CRD) with treatments replicated five (5) times. Place and Duration of Study: Screenhouse of the Department of Agronomy, University of Ibadan, Nigeria, between July to November 2016. Methodology: Six levels of kolgrace organic fertilizer were used (0.00, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…The biofertilizer is affordable and readily available. Earlier report by Ihejiofor et al (2020) indicated that 0.5 t ha -1 of Kolgrace bio-fertilizer gave best results for growth and yield traits of greengram evaluated in the screenhouse. This research was therefore carried out to investigate the best rate of Kolgrace bio-fertilizer for greengram production under field conditions in Ibadan, Nigeria, a derived savanna agro-ecological zone.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…The biofertilizer is affordable and readily available. Earlier report by Ihejiofor et al (2020) indicated that 0.5 t ha -1 of Kolgrace bio-fertilizer gave best results for growth and yield traits of greengram evaluated in the screenhouse. This research was therefore carried out to investigate the best rate of Kolgrace bio-fertilizer for greengram production under field conditions in Ibadan, Nigeria, a derived savanna agro-ecological zone.…”
Section: Introductionmentioning
confidence: 87%
“…Each block was sub-divided into plots on which seedbeds were made, with each plot measuring 1.0 × 1.8 m. The treatments comprised five application rates of an indigenous bio-fertilizer (Kolgrace); 0.00, 0.25, 0.50, 1.00 and 2.00 t ha -1 arranged in a randomized complete block design, and replicated four times. The selected treatment rates were informed by a preceding screenhouse study by Ihejiofor et al (2020), where six Kolgrace rates (0.00, 0.50, 1.00, 2.00, 4.00 and 8.00 t ha -1 ) were evaluated for growth and yield attributes, with 0.5 t ha -1 emerging as the best while 4 and 8 t ha -1 seemed wasteful, and repressed growth and yield. Rates above 0.5 t ha -1 were seen to have suppressed growth and yield, hence the inclusion of 0.25 t ha -1 in the current study.…”
Section: Field Preparation Treatments and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil pH was determined following [19], exchangeable K [20], organic carbon [21] and thereafter multiplied by 1.724 to obtain soil organic matter, available P [22], and Total Nitrogen by macro Kjeldahl method [23]. Chemical analyses of the manures were determined following the procedures of [24].…”
Section: Soil Chemical and Manure Analysismentioning
confidence: 99%